Profile: The Kenya Multi-Site Serosurveillance (KEMIS) collaboration [version 2; peer review: 2 approved] - Peninah Munyua; J. Anthony G. Scott; Amy Herman-Roloff; Shirine Voller; Abdhalah K. Ziraba; Patrick K. Munywoki; E. Wangeci Kagucia; Dickens Onyango; D. James Nokes; Godfrey Bigogo; Kimani Makobu; Cameline Orlendo; et al. (Gates Open Research)
The Kenya Multi Site Serosurveillance (KEMIS) collaboration set out to implement an integrated, nationally representative, population-based program of serological surveillance for past infection for a number of important infectious diseases in Kenya. The project started in December 2021 and built on a portfolio of SARS-CoV-2 research conducted in 2020 and 2021. In this profile paper, we describe the background of the KEMIS collaboration, its aim and objectives, the Health and Demographic Surveillance System sites that were involved in data collection, and the key activities undertaken. We also explain how we established governance and management of the KEMIS collaboration, and reflect on opportunities, challenges, lessons learned, and future directions.